Biomarkers in the diagnostic algorithm of myalgic encephalomyelitis/chronic fatigue syndrome - Gravelsina, Sabine; Vilmane, Anda; Svirskis, Simons; Rasa-Dzelzkaleja, Santa; Nora-Krukle, Zaiga; Vecvagare, Katrine; Krumina, Angelika; Leineman, Iana; Shoenfeld, Yehuda; Murovska, Modra (Frontiers in Immunology, 2022)
ME/CFS is a complex disease that is mainly diagnosed based on its’s clinical symptoms. Biomarkers that could facilitate the diagnosis of ME/CFS are not yet available, therefore reliable and clinically useful disease indicators are of high importance. The aim of this work was to analyse association between ME/CFS clinical course severity, presence of HHV-6A/B infection markers and plasma levels of autoantibodies against adrenergic and muscarinic acetylcholine receptors. 134 patients with ME/CFS and 33 healthy controls were analysed for the presence of HHV-6A/B using PCRs, antibodies against beta2-adrenergic receptors (β2AdR) and muscarinic acetylcholine receptors (M3 AChR and M4 AChR) using ELISAs. HHV-6A/B U3 genomic sequence in whole blood DNA was detected in 19/31 patients with severe ME/CFS, in 18/73 moderate and in 7/30 mild ME/CFS cases. Severity-related differences were found among those with virus load more than 1000 copies/106 PBMC. Although no disease severity-related differences in anti-β2AdR levels were observed in ME/CFS patients, median concentration of these antibodies in plasma samples of ME/CFS patients was 1.4 ng/mL, while in healthy controls 0.81 ng/mL with statistically significant increased level in those with ME/CFS (p = 0.0103). Significant difference of antibodies against M4 AChR median concentration was found between ME/CFS patients (8.15 ng/mL) and healthy controls (6.45 ng/mL) (p = 0.0250). The levels of anti-M4 plotted against disease severity did not show any difference, however increased viral load correlates with the increase in anti-M4 level. ME/CFS patients with high HHV-6 load have a more severe course of the disease thus confirming that the severity of the disease depends on the viral load - the course of the disease is more severe with a higher viral load. Increase in anti-M4 AchR and anti-β2AdR levels is detected in all ME/CFS patients’ groups in comparison to control group not depending on ME/CFS clinical course severity. However, the increase in HHV-6 load correlates with the increase in anti-M4 level and increase in anti-M4 level in turn is associated with increase in anti-β2AdR level. Elevated levels of antibodies against β2AdR and M4 receptors in ME/CFS patients support their usage as clinical biomarkers in the diagnostic algorithm of ME/CFS.